2002
DOI: 10.1002/art.10558
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for immunologic laboratory testing in the rheumatic diseases: Anti‐DNA antibody tests

Abstract: This paper is part of a series on immunologic testing guidelines. The series introduction (1) outlines the full methodology for obtaining data, grading the literature, combining the information from multiple sources, and developing recommendations. Briefly, MEDLINE and Healthstar were searched using a variety of search terms, and all relevant available literature was reviewed. All papers were critically reviewed using published standards for studies of diagnostic tests. Test use was categorized as primarily di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
122
0
5

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(133 citation statements)
references
References 85 publications
(127 reference statements)
6
122
0
5
Order By: Relevance
“…Detection of this type of antinuclear antibodies is highly suggestive of SLE disease, but a negative result of these antibodies in patient's specimen does not exclude the presence of such a disease (Habash-Bseiso et al, 2005). Possible occurrence of anti-dsDNA antibody in asymptomatic lupus patients should pay attention that this test should not be relied upon as a definite parameter to follow up disease activity (Kavanaugh and Solomon, 2002 Table 4 shows sensitivity and specificity of antidsDNA test in lupus nephritis patients using ELISA test. It was clearly demonstrated that sensitivity and specificity of the test were 74 and 100%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Detection of this type of antinuclear antibodies is highly suggestive of SLE disease, but a negative result of these antibodies in patient's specimen does not exclude the presence of such a disease (Habash-Bseiso et al, 2005). Possible occurrence of anti-dsDNA antibody in asymptomatic lupus patients should pay attention that this test should not be relied upon as a definite parameter to follow up disease activity (Kavanaugh and Solomon, 2002 Table 4 shows sensitivity and specificity of antidsDNA test in lupus nephritis patients using ELISA test. It was clearly demonstrated that sensitivity and specificity of the test were 74 and 100%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Антитела к ДНК являются серологическим маркером СКВ. Антитела к дсДНК более специфич-ны для диагностики СКВ, чем антитела к осДНК, которые присутствуют в сыворотках больных при других РЗ и не имеют существенного диагностиче-ского значения (А) [4,12].…”
Section: аутоантителаunclassified
“…При поло-жительных результатах ИФА антител к дсДНК ре-комендуется проведение подтверждающих тестов, 6. Положительные результаты обнаружения ан-тител к дсДНК не позволяют достоверно прогнози-ровать обострения СКВ (А) [12].…”
Section: аутоантителаunclassified
See 1 more Smart Citation
“…These autoantibodies were later found to be valuable for the diagnosis of SLE as they are rarely found in sera of healthy controls or patients with other autoimmune diseases (apart from autoimmune hepatitis), but are found in many SLE patients at least sometime during their disease course [132,133]. However, the reported frequencies of anti-dsDNA positive SLE patients is highly varying and seems dependent on method of anti-dsDNA assessment and the disease severity of the patients [133].…”
Section: Anti-dsdnamentioning
confidence: 99%